2008
DOI: 10.1097/md.0b013e3181881354
|View full text |Cite
|
Sign up to set email alerts
|

Young-Onset Colorectal Cancer in Patients With No Known Genetic Predisposition

Abstract: Early recognition of colorectal cancer (CRC) in young patients without known genetic predisposition is a challenge, and clinicopathologic features at time of presentation are not well described. We conducted the current study to review these features in a large population of patients with young-onset CRC (initial diagnosis at age ≤50 yr without established risk factors). We reviewed the records of all patients aged 50 years or younger diagnosed with a primary CRC at our institution between 1976 and 2002. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
164
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(183 citation statements)
references
References 13 publications
16
164
2
1
Order By: Relevance
“…This percentage is similar to that reported in Jordan (20.2%) (Al-Jaberi et al, 2003), and Egypt (22%) (Veruttipong et al, 2012). Noteworthy, in western population, the incidence of the disease has increased in the 30-39 years group at an annual rate of 3% in men and 2% in women from 1992 to 2005 (Siegel et al, 2009) Some studies suggest that young CRC patients are diagnosed more frequently in advanced stage (Dozois et al, 2008). A publication based on the SEER database has demonstrated a higher frequency of stage III and IV disease in younger compared to older patients that was highly statistically significant (O'Connell et al, 2004a).…”
Section: Introductionsupporting
confidence: 73%
“…This percentage is similar to that reported in Jordan (20.2%) (Al-Jaberi et al, 2003), and Egypt (22%) (Veruttipong et al, 2012). Noteworthy, in western population, the incidence of the disease has increased in the 30-39 years group at an annual rate of 3% in men and 2% in women from 1992 to 2005 (Siegel et al, 2009) Some studies suggest that young CRC patients are diagnosed more frequently in advanced stage (Dozois et al, 2008). A publication based on the SEER database has demonstrated a higher frequency of stage III and IV disease in younger compared to older patients that was highly statistically significant (O'Connell et al, 2004a).…”
Section: Introductionsupporting
confidence: 73%
“…Another study showed an average age at presentation (54.2 ± 16.25 years) that was statistically less than that of AC patients (mean age at presentation: 58.73 ± 13.62 years) (32). Dozois et al demonstrated that MC patients had an average age at presentation of 42.2 years (33). Interestingly, rectal cancers were more frequent under the age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…It is relatively rare to find such tumours in the rectum, being most commonly found in the proximal colon. One of the largest studies examining the outcomes of mucinous tumours investigated 16,991 patients and found that just over 18 % of all mucinous tumours were found in the rectum compared with 29 % of non-mucinous tumours [9]. A recent meta-analysis of outcomes in mucinous colon cancer, which included some studies with rectal tumours, reported that mucinous tumours were more frequently found proximal to the splenic flexure compared to non-mucinous adenocarcinoma [10].…”
Section: Epidemiology and Clinical Characteristicsmentioning
confidence: 99%
“…A study by Dozois et al [16], which investigated the characteristics of colon and rectal cancer in patients below the age of 50, found that patients with mucinous tumours had a mean age at presentation of 42.2 years. Furthermore, rectal cancers were found to be more common below the age of 50 (49.1 vs. 21.9 %).…”
Section: Epidemiology and Clinical Characteristicsmentioning
confidence: 99%